2007
DOI: 10.1007/s10750-007-9254-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Potamogeton crispus growth on nutrients in the sediment and water of Lake Tangxunhu

Abstract: An incubation experiment was performed on Potamogeton crispus (P. crispus) using sediment collected from Lake Tangxunhu in the center of China, in order to determine the effects of plant growth on Fe, Si, Cu, Zn, Mn, Mg, P, and Ca concentrations in the sediments and overlying waters. After 3 months of incubation, Ca, Mg, and Si concentrations in the water column were significantly lower, and P and Cu concentrations were significantly higher than in unplanted controls. The effect of P. crispus growth on sedimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Afterwards, the sediment morphology was observed under a JSM-6390LV SEM (Komatsu NTC Ltd., Japan). At the same time, the composition and relative levels of the elements in the sediments were measured using INCA EDX (Oxford Instruments, England) (Mi et al 2008). …”
Section: Sem-edx Characterization Of Coprecipitate Samplesmentioning
confidence: 99%
“…Afterwards, the sediment morphology was observed under a JSM-6390LV SEM (Komatsu NTC Ltd., Japan). At the same time, the composition and relative levels of the elements in the sediments were measured using INCA EDX (Oxford Instruments, England) (Mi et al 2008). …”
Section: Sem-edx Characterization Of Coprecipitate Samplesmentioning
confidence: 99%
“…Concentrations of most elements measured in the water were below our method detection limits probably because they were sequestered by macrophytes and plankton (Guilizzoni 1991; Horppila and Nurminen 2003; Mi et al 2008) or bound to organic matter and suspended particles (Golterman 1969; APHA 1994). Physical and chemical characteristics of the sediments in our lakes may also have influenced the diffusion of elements from the sediment to water column and vice versa (Jaynes and Carpenter 1986).…”
Section: Discussionmentioning
confidence: 67%
“…Most earlier studies focused on the cycling of nutrients such as phosphorus, nitrogen, and dissolved organic carbon in lakes (Barko and Smart 1980; Downing and McCauley 1992; Medeiros et al 2012; Wu et al 2014), but a few have included other elements such as Cd, Cr, Cu, Fe, Mn, Ni, Pb, Si, and Zn (St. Cyr et al 1994; Thorbergsdottir and Gislason 2004; Mi et al 2008). Some research has explored how nutrients in lakes relate to nearby land use (Fraterrigo and Downing 2008; Wezel et al 2013) and phytoplankton biomass (Grace et al 2010; Borics et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Lakes with lower transparency were distinguished from the group of lakes with a high degree of overgrowth by intensity of phytoplankton blooms. In contrast, Søndergaard and Moss [50] highlighted negative effects of submerged macrophytes on phytoplankton productivity and enhanced nutrient loadings within macrophyte beds [51,52]. However, detailed analysis of macrophytes showed that the impact on their condition resulted less from the presence of submerged macrophytes but, rather, from their congested form and species composition.…”
Section: Trophy Of Overgrowing Lakesmentioning
confidence: 98%